Distribution of cyanogenic potential in the cassava germplasm - Bokanga, M. (International Society for Horticultural Science, 1994)
Cassava is a cyanogenic plant which accumulates linamarin and lotaustralin in its tissues. The ability of damaged tissues to release hydrogen cyanide from linamarin and lotaustralin is at the origin of cassava's cyanogenic potential. The cyanogenic potential of a large number of cassava varieties found in Nigeria, in Cameroon and in the cassava breeding program of the International Institute of Tropical Agriculture, Ibadan, Nigeria has been determined. The distribution of the cyanogenic potential character in these varieties has been found to be positively skewed and to follow a lognormal function. This means that in nature there is probably a greater preponderance of low cyanogenic potential cassava varieties. This conclusion is in agreement with findings at the Centro International de Agricultura Tropical which holds the world cassava collection. The variation in cyanogenic potential between roots and leaves of the same plant, between plants of the same varieties and between varieties are also discussed. Implications for sampling and statistical analysis of data on cyanogenic potential from field trials are presented. The correlation between bitterness in cassava and cyanogenic potential was found to be high, but a cause-effect relationships is questionable.